Intelligibility in 3-Year-Olds With Cleft Lip and/or Palate Using the Intelligibility in Context Scale: Findings from the Cleft Collective Cohort Study. (September 2021) - Seifert, Miriam; Davies, Amy; Harding, Sam; McLeod, Sharynne; Wren, Yvonne
Objective: To provide comparison data on the Intelligibility in Context Scale (ICS) for a sample of 3-year-old English-speaking children born with any cleft type. Design: Questionnaire data from the Cleft Collective Cohort Study were used. Descriptive and inferential statistics were carried out to determine difference according to children's cleft type and syndromic status. Participants: A total of 412 children born with cleft lip and/or palate whose mothers had completed the ICS when their child was 3 years old. Main Outcome Measure(s): Mothers' rating of their children's intelligibility using the ICS. Results: The average ICS score for the total sample was 3.75 ( sometimes-usually intelligible; standard deviation [SD] = 0.76, 95% CIs = 3.68-3.83) of a possible score of 5 ( always intelligible). Children's speech was reported to be most intelligible to their mothers (mean = 4.33, SD = 0.61, 95% CIs = 4.27-4.39) and least intelligible to strangers (mean = 3.36, SD = 1.00, 95% CIs = 3.26-3.45). There was strong evidence ( P < .001) for a difference in intelligibility between children with cleft lip only (n = 104, mean = 4.13, SD = 0.62, 95% CIs = 4.01-4.25) and children with any form of cleft palate (n = 308, mean = 3.63, SD = 0.76, 95% CIs = 3.52-3.71). Children born with cleft palate with or without cleft lip and an identified syndrome were rated as less intelligible (n = 63, mean = 3.28, SD = 0.85, 95% CIs = 3.06-3.49) compared to children who did not have a syndrome (n = 245, mean = 3.72, SD = 0.71, 95% CIs = 3.63-3.81). Conclusions: These results provide preliminary comparative data for clinical services using the outcome measures recommended by the International Consortium for Health Outcomes Measurement.